Plurality of Creatures and the Oneness of the Creator - Nurul Mawaddah; Andi Aderus; Muhammad Hudain (Universitas Muhammadiyah Palu, 2025)
This study discusses the relationship between the plurality of beings and the oneness of the Creator from philosophical and theological perspectives. The plurality of beings reflects the diversity of God's creation, which includes humans, animals, plants, and inanimate objects, as manifestations of the greatness and complexity of the Creator. This study uses a qualitative method with a phenomenological approach and content analysis to understand the interaction between the diversity of creation and the oneness of God. Data were collected through literature studies, interviews with religious figures, and observations in religious communities. The analysis was conducted hermeneutically to interpret religious and philosophical texts, as well as through thematic analysis to identify patterns of thought. The results show that the plurality of beings not only affirms the oneness of God but also encourages tolerance, interfaith dialogue, and social harmony in pluralistic societies. By understanding this relationship, society can create strong social cohesion and reduce the potential for identity-based conflicts.